Proceedings of the 2nd Annual Conference on Education and Social Science (ACCESS 2020) 2021
DOI: 10.2991/assehr.k.210525.038
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Utilization of Village Fund on Family Welfare in Buleleng District, Bali

Abstract: Development in the village is a participatory development model, which is a joint development management system, which is planned, implemented, and evaluated through deliberation, consensus, and cooperation. The objectives of this study are first to analyze the direct effect of community participation, intellectual capital, the role of the government on the use of village funds, village economic performance, and family welfare, second to analyze the direct effect of the use of village funds and village economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…This program has the strong purpose of increasing the income per capita in the rural areas; hence, the discrepancy between the economic conditions in the city and village areas would be able to be reduced if mainly related to the income that each member obtains. According to the study completed by Diatmika [39], A research study entitled "The Effect of the Utilization of the Village Fund on the Family's Prosperity in Buleleng Regency, Bali Province" found that the most direct and meaningful participation that the communities could make was to actively participate in the empowerment programs. The Besides, the community empowerment program is able to support the long-term qualification of the community members to acquire their individual income independently and to avoid poverty, hence growing the economy of the village areas.…”
Section: The Effectiveness Of the Village Funding Program On The Econ...mentioning
confidence: 99%
“…This program has the strong purpose of increasing the income per capita in the rural areas; hence, the discrepancy between the economic conditions in the city and village areas would be able to be reduced if mainly related to the income that each member obtains. According to the study completed by Diatmika [39], A research study entitled "The Effect of the Utilization of the Village Fund on the Family's Prosperity in Buleleng Regency, Bali Province" found that the most direct and meaningful participation that the communities could make was to actively participate in the empowerment programs. The Besides, the community empowerment program is able to support the long-term qualification of the community members to acquire their individual income independently and to avoid poverty, hence growing the economy of the village areas.…”
Section: The Effectiveness Of the Village Funding Program On The Econ...mentioning
confidence: 99%